the Perspektif Teologis terhadap Fenomena Perjalanan Spiritual sebagai Bentuk Slow Tourism di Provinsi Jawa Timur: Perspektif Teologis terhadap Fenomena Perjalanan Spiritual sebagai Bentuk Slow Tourism di Provinsi Jawa Timur - Dananjaya, Ahmad Ghazy (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study analyzes the influence of Spiritual Motivation and Search for Meaning in Life on Tourist Inner Satisfaction within the framework of Slow Tourism in East Java. Responding to the crisis of modern spirituality, slow tourism emerges as an antithesis to mass tourism, offering a theological contemplation space. This study applies a Mixed Method with a Sequential Explanatory strategy. Quantitative data were collected from 200 respondents at spiritual sites in East Java using a 1-7 Likert scale questionnaire, followed by qualitative deepening through interviews. Regression analysis and data triangulation confirmed that Spiritual Motivation and Search for Meaning in Life have a positive and significant effect on Inner Satisfaction. These findings validate the theological perspective that tourism is not merely physical mobility, but an existential pilgrimage towards transcendence that presents the highest inner satisfaction (Ananda). The implications recommend integrating sacred values in destination management to facilitate the soul recovery of tourists suffering from alienation due to modernity.